2021
DOI: 10.3389/fendo.2021.715043
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Post-Pancreatitis Diabetes Mellitus and Cystic Fibrosis-Related Diabetes: A Review of Preclinical Studies

Abstract: Anatomical proximity and functional correlations between the exocrine and endocrine pancreas warrant reciprocal effects between the two parts. Inflammatory diseases of the exocrine pancreas, such as acute or chronic pancreatitis, or the presence of cystic fibrosis disrupt endocrine function, resulting in diabetes of the exocrine pancreas. Although novel mechanisms are being increasingly identified, the intra- and intercellular pathways regulating exocrine–endocrine interactions are still not fully understood, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 163 publications
0
8
0
Order By: Relevance
“…The effect of exocrine pancreas on endocrine function under physiological conditions can be reflected in the inhibitory effect of amylase and lipase on insulin secretion. One possible explanation is a regulatory mechanism that acts against insulin overproduction and keeps it at a normal level and further avoids exhaustion of β cells ( 11 ). In addition to the regulation of insulin secretion, trypsin may also be involved in islet formation and differentiation ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The effect of exocrine pancreas on endocrine function under physiological conditions can be reflected in the inhibitory effect of amylase and lipase on insulin secretion. One possible explanation is a regulatory mechanism that acts against insulin overproduction and keeps it at a normal level and further avoids exhaustion of β cells ( 11 ). In addition to the regulation of insulin secretion, trypsin may also be involved in islet formation and differentiation ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…A recently published systematic review and meta-analysis by our workgroup reported that new-onset diabetes occurred in 23% of patients with AP ( 9 ), in line with previous research conducted by Das et al ( 10 ). However, other studies provided inconsistent prevalence rates ( 11 ). In particular, few studies provide insight into the frequency of PPDM-A in Chinese patients ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-pancreatitis diabetes mellitus (PPDM) is a frequent complication of pancreatitis, as hyperinsulinemia during pancreatitis might be responsible for the development of insulin resistance (IR) (153). Acute pancreatitis is an acute abdominal inflammatory disease associated with necrosis of the pancreas, systemic inflammation, multiple organ dysfunction, and mechanistically related to a cytosolic calcium overload (154) whereas chronic pancreatitis is a progressive syndrome characterised by pancreatic inflammation, leading to extensive tissue fibrosis and deficiency of pancreatic exocrine and endocrine function (155).…”
Section: Mirnas In Diabetes Linked To Pancreatitismentioning
confidence: 99%
“…Pancreatic inflammatory diseases, including acute or chronic pancreatitis, could result in diabetes ( Gál et al, 2021 ). Pancreatic inflammation has been found to be promoted by the overexpression of miR-29 in β cells of βTG mice ( Sun et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%